Class Acts : Derrida on the Public Stage - Naas, Michael (Book collections on Project MUSE., 2021)
Class Acts looks at two often neglected aspects of Derrida's work as a philosopher, his public lectures and his teaching, along with the question of the ""speech act"" that links them, that is, the question of what one is doing when one speaks in public in these ways.